Moderasi Pemberdayaan Psikologis pada Hubungan Kepemimpinan Autentik terhadap Perilaku Kerja Inovatif - H. Jeily Syahputra; Ririn Handayani; Adolf Bastian (CV. ITTC INDONESIA, 2026)
This research was conducted at the Pekanbaru City District Court with the aim of analyzing the role of psychological empowerment as a moderating variable in the relationship between authentic leadership and innovative work behavior. The study population consisted of 95 individuals, all of whom were sampled using a saturated sampling method. Primary data were obtained through a questionnaire using a 5-point Likert scale (1–5), covering the research variables. Subsequently, the data were analyzed using a Structural Equation Modeling (SEM) approach using SmartPLS 3.0 software. The research findings indicate that authentic leadership exhibits a positive relationship with innovative work behavior, and psychological empowerment has been shown to moderate the relationship between authentic leadership and innovative work behavior.